Role of the State in Partnerships with the Private Sector. (January 2016) - Verma, Manisha
Abstract: The State, as we know, has been transforming in many ways. From a unitary and predominantly hierarchical entity perceived to be almost 'dictatorial' by many, it is seen to be forging coalitions and partnerships with varied non-State actors ostensibly to benefit from their expertise, resources and knowledge to achieve public goals. These partners include the private sector, NGOs, civil society organisations, practitioners, experts and academicians. Such partnerships (e.g., public–private partnerships or PPPs) are an emerging feature of public policy around the world. While some analysts believe that this implies 'decline of the State' or what is popularly termed as 'State failure' with the State ceding its powers to non-State actors, others are of the view that these forms of new governance indicate a collective policy process where governing is accomplished with and through what are known as 'policy' or 'governance' networks. The new definition of governance lays stress on a 'centreless society' in a polycentric State defined by multiple actors and differentiated polity. An emerging body of evidence, however, suggests that when entities with distinct agenda, motivation, priorities, values, ethics and ideologies (based on the normative and conventional division of roles) come together for the achievement of State-directed goals, not only do the role and responsibilities of the State get transformed, but there emerge several public policy and governance issues. The partnerships, due to their multi-actor and multi-form structures, are observed in many cases to lead to indeterminate outcomes, exclude vulnerable and unrepresented sections, result in agency capture and tend to steer policies towards own selves. There is growing consensus in literature for an enhanced role of the State in the governance of networks, rather than a diminished role. The article will provide theoretical insights into what are the factors that have contributed to this transformation in governance, policy challenges in the partnerships with the private actors and highlight the redefined roles and responsibilities of the State agencies within these new forms of governance.